Study of Acceptance of Retribution for Cleaning Services in Pematang Serai Village, Langkat Regency - Dito Aditia Darma Nasution; Meigia Nidya Sari; Annisa Fajariah Damanik (Universitas 17 Agustus 1945 Semarang, 2023)
This study raises the phenomenon of the effectiveness of receiving cleaning service retribution in Pematang Serai Village, Langkat Regency. The reason for this research was that the acceptance of cleaning service retribution for Langkat Regency from 2014 to 2020 was still not optimal and had not been able to reach the targets set each year, so it was necessary to conduct research to measure the effectiveness of receiving cleaning service retribution with an analysis of the principles of good governance. This study uses qualitative research methods with data collection techniques through interviews and documentation. Meanwhile, data analysis techniques used data reduction, data presentation, and drawing conclusions. The research results show that the level of effectiveness of cleaning service retribution from 2017 to 2020 has an average of 73%, based on effectiveness criteria or indicators it can be judged that the level of effectiveness of cleaning service retribution is included in the Less Effective category. The application of the Good Governance Principles for cleaning service retribution has not been implemented perfectly and still needs to be improved.